Impact of Environmental Factors on the Moss Banks’ State in Argentine Islands (West Antarctica): Interannual Monitoring - Puhovkin, Anton; Yevchun, Hanna; Bartak, Milos; Hajek, Josef; Shepeta, Yuri; Miryuta, Natalia; Parnikoza, Ivan (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):286